Assinaturas estromais e expressão de microRNAs relacionados à angiogênese em linfomas não-Hodgkin difuso de grandes células B - Borges, Natalia Morais [UNIFESP] (2014)
Diffuse large B-cell lymphoma (DLBCL) is the most frequent aggressive non-Hodgkin lymphoma (NHL) and, despite advances in treatment, 30% of the cases are refractory or relapse after chemoimmunotherapy. Currently, the relationship between angiogenesis and angiomiRs in DLBCL is unknown. We classified 84 DLBCL according to stromal signatures using tissue microarray and immunohistochemistry (CD34, CD68 and SPARC). We also evaluated the expression of pro- and antiangiomiRs in paraffin embedded tissues of DLBCL by real-time PCR and correlate them with MVD. Approximately 40% of cases were classified as stromal-1, 50% were classified as stromal-2 and 10% were not classified. We observed increased expression of pro-angiomiRs Let-7f, miR-17, miR-18a, miR-19b, miR-126, miR-130a, miR-210, miR-296 and miR-378 in 14%, 57%, 30%, 45%, 12%, 12%, 56%, 58% and 48% of cases, respectively. Among antiangiomiRs we found decreased expression of miR-16, miR-20b, miR-92a, miR-221 and miR-328 in, respectively, 27%, 71%, 2%, 44% and 11%. When comparing the expression of angiomiRs with molecular subtypes according to the algorithm Hans et al. (2004) we found association between increased expression pro-angiomir miR-126, pro-angiomir miR-130a e antiangiomir miR-328 and the subtype ABC (non-GCB). However, only in the case of angiomiRs miR-16, miR-221 and miR-328 we were able to verify expression values compatible with angiogenesis, i.e., higher levels of the three antiangiomiRs in patients with low MVD and stromal-1 signature. The median overall survival has not been reached, with a maximum follow-up of 146.5 months. We observed worse outcome in Ann Arbor stage III/IV, high IPI and CD34 Quartiles III/IV (automated counting). IPI and CD34 confirmed independent impact on survival of the study group. Patients with high-risk IPI showed probability of evolving to death 3.4 times greater than the rest of the group and patients with higher MVD as automated counting (Quartiles III and IV) had chance of evolving to death two times higher than the rest of the group. MicroRNAs showed no prognostic significance in independent serum samples? cohort. Therefore, the stromal-2 signature was found in 50% of cases. We confirmed association between antiangiomirs miR-16, miR-221 and miR-328 and stromal-1 signature. Four angiomiRs emerge as potential therapeutic targets (differentially expressed in ~50% of cases): pro-angiomiRs miR-17, miR-210 and miR-296 and anti-angiomiR miR-20b. Although the four microRNAs seem to be important in DLBCL pathogenesis, they are not predictive of DLBCL onset or relapse.